Basketball without borders a comparative analysis of the coverage of the Philippine Star and Slam Philippines magazine of the National Basketball Association (NBA) and the Philippine Basketball Association (PBA) - Morales, Mikael Mari Reyes 1992- (2014)
"The study is guided by the theory of globalization and framing. It looks at how globalization influences and creates differences in the media coverage of global and local sports. The study presents how a globally known league such as the National Basketball Association affects the coverage of a local league such as the Philippine Basketball Association. The study analyzed articles written by The Philippine Star and SLAM Philippines during the months of November through May during the 2012-2013 seasons of the NBA and PBA. The study focuses on frequency and prominence of NBA and PBA articles in The Philippine Star and SLAM Philippines to measure whether globalization affects the framing of such news. Frequency focuses on the number of articles published about both leagues. Prominence focuses on the type of article, use of images, length of article, and the position of the article and its headline. Both of these aspects come from the assumption that the increases globalization of the NBA creates a preference to cover the NBA compared to the PBA."